Error analysis for a monolithic discretization of coupled Darcy and Stokes problems - Girault, Vivette; Kanschat, Guido; Rivière, Béatrice (Journal of numerical mathematics, 2014)
The coupled Stokes and Darcy equations are approximated by a strongly conservative finite element method. The discrete spaces are the divergence-conforming velocity space with matching pressure space such as the Raviart-Thomas spaces. This work proves optimal error estimate of the velocity in the L2 norm in the domain and on the interface. Lipschitz regularity of the interface is sufficient to obtain the results.